The Role of Innovation Management in Creative Economy-Based Product Development in West Java Province - Nur Hakim; Juni iswanto; Eko Sudarmanto (Westscience Press, 2024)
This study conducts a comprehensive bibliometric analysis of the field of entrepreneurial ecosystems, mapping the evolving landscape of research from 1995 to 2024. Utilizing VOSviewer for visual network analysis, the research identifies central themes, examines co-authorship and institutional collaboration networks, and highlights the temporal progression of key topics. The findings reveal